Development of new systematic techniques for retrofit of water network - Tan, Yin Ling (2005)
Grassroots synthesis of maximum water recovery network based on Pinch Analysis has been rather well established. In contrast, less work has been done on retrofit of water network. There is a clear need to develop procedures to retrofit an existing water network. Four new systematic techniques for retrofit of water network based on Pinch Analysis concept have been developed in this work, i.e. retrofit of water network for mass transfer-based operations; retrofit of water network for nonmass transfer-based operations; retrofit of water network with regeneration unit(s) optimisation; retrofit of water network with the addition of new regeneration unit(s). Retrofit technique for water network with mass transfer-based operations involves two key steps namely utility targeting and network design. During targeting, utility and capital cost targets were determined for a particular capital expenditure. Lastly, the existing network was retrofitted to meet the targets. Retrofit method for nonmass transfer-based operations precludes targeting and only requires retrofit design. A new graphical tool called concentration block diagram (CBD) has been introduced to diagnose, retrofit and evolve the existing water network. The new techniques proposed for retrofit of water network with existing regeneration unit(s) optimisation/ additional new regeneration unit(s) consist of two stages. The first stage locates the various retrofit targets, where utility savings and capital investment were determined for a range of process parameters (i.e. total flowrate and/or outlet concentration of the regeneration unit). Next, the existing water network was redesigned to achieve the chosen targets. Application of the new retrofit techniques on paper mill plants proves that the techniques are both highly interactive as well as viable for implementation.